KAMPANYE SOSIAL PENERAPAN GAYA HIDUP MINIMALIS TERHADAP WANITA DI KOTA PALEMBANG - Euis Febriyanti Hidayat; Bobby Halim; Aji Windu Viatra (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract: The fulfillment of individual life needs cannot be separated from people's consumption of an item. But along with the times, the behavior patterns of people who originally shopped to meet their needs changed to shopping beyond their needs, which is often called consumerism. The existence of consumerism in society is supported by the development of a modern era that has an impact on lifestyle changes. Therefore, a social campaign was carried out to implement a minimalist lifestyle in reducing consumptive behavior and impulse shopping. This design uses the Design Thinking method which consists of Emphatize (understanding the problem), Define (analyzing data), Ideate (determining concept ideas), Prototype (visualizing ideas), and Test ( testing the results) so that the results of designing a media work are obtained namely the main media in the form of motion graphics, issue media in the form of posters, infographics, x-banners, Instagram feeds, catalogs, and supporting media in the form of keychains, rags, beeswax wrap, t-shirts, tumblers, tote bags and notebooks. With this social campaign, it is expected to provide information about a minimalist lifestyle applied in everyday life and can be wiser in buying goods according to their functions.